Kitchen top machine for cleaning juicing carrots - Teoh, Qi En (2017)
Carrot is widely grown around the world due to its rich nutritional value that is necessary to the human. According to the research, most of the goodness and nutrients such as antioxidant compounds lies just underneath the carrot peel. However, the carrot peel is well prone to dirt and soil as the carrot is a root vegetable and it is grown underground. Thus, the cleaning of the carrot peel is an important post process after the harvest. Although carrots will be usually cleaned before going into the market, there are chances that foreign material and dirt still remain on the carrot peel when it is being sold. Hence, a kitchen top device is to be designed to clean the carrot at home before consumption. The purpose of this project is to generate a design of a manually operated kitchen top device for cleaning juicing carrots. In the early design process, a systematic approach has been adopted to generate function analysis, morphological chart, concept evaluation, and the concept selection. The selected conceptual design utilized spiral drive mechanism as the driving mechanism to clean the carrot. The device consists of two parts, which includes the upper unit and the lower unit. The upper unit comprises the spiral drive mechanism that drives the cleaning components, namely the rollers to fulfil the function of cleaning. Whereas the lower unit is responsible for keeping the carrot in place and containing water when the cleaning operation is being carried out. The prototype has been built to prove the feasibility of the spiral drive mechanism. The mechanism was proven to function as desired and a test was done to ascertain the minimum force required to operate the device. It was verified that the minimum operating force lies within the acceptable range. Lastly, some recommendations for future work have been brought out to enhance the design of the device in the future.